The Police Effect. The Police Episteme like Modernity - Karmy Bolton, Rodrigo (Re-presentaciones: Periodismo, comunicación y sociedad, 2020)
The work has a series of theoretical elements that aim at a joint questioning of both the notion of sovereignty and the police character in which it is deployed. In this way, modern sovereignty policing guarantees the reproduction of order as a permanent assembly lacking in substance and support. Secondly, the text shows how sovereignty is configured in police terms on the basis of a logic of effects management. Finally, the notion of image is used as a concept that, under the prism of representation, allows sovereignty to be erected in the form of a spectacle that mediates and stages a type of subject docile to its rationality.
Keywords: Police; surface; image